Exploring noun bias in Filipino-English bilingual children - Lucas, Rochelle Irene G. (Animo Repository, 2008)
Researchers have suggested that there is a noun bias in children's early vocabularies brought about by features of adults' child-directed utterances, which may vary across languages (E. V. Bates et al., 1994; D. Gentner, 1982). In the present study, the authors explored noun bias in 60 Filipino-English bilingual children whose 2 languages differed in how they emphasized nouns and verbs in typical syntactic forms. The results revealed a noun bias, but only in the bilingual children's English vocabulary. The noun bias in English was associated with the frequency of nouns in the caregivers' utterances and the proportion of nouns in the initial positions of the caregivers' utterances. The authors also found different associations between salient positions in the adult utterances and children's vocabularies in English and Filipino. Copyright © 2008 Heldref Publications.